Intrapartum transfers from the Birth Centre to the Obstetric Unit in 2017 – analysis of reasons - Łukasiewicz, Aleksandra; Baranowska, Barbara; Dzierżak-Postek, Edyta; Węgrzyn, Piotr (Nursing in the 21st Century, 2019)
INTRAPARTUM TRANSFERS FROM THE BIRTH CENTRE TO THE OBSTETRIC UNIT IN 2017 – ANALYSIS OF REASONS Introduction. The standard of perinatal care gives the woman the right to consciously choose the place of birth. Birth Centres (BC) run by midwives implement a vision of a non-medicalized birth in intimate homelike conditions. Aim. The aim of the study is to determine the causes of transfers from the Birth Centre to the Obstetric Unit and to indicate the social and demographic characteristics of the women giving birth that may predispose to transfer. Material and methods. The study was based on the analysis of the medical records of women who were transferred from the BC to the St. Sophia Obstetric Unit in Warsaw. 88 women who were transferred constituted the study group. Results. The most numerous group were women giving birth aged 30-34. The majority were giving birth for the first time and had higher education. Intrapartum transfers were related to the mother‘s obstetric condition, fetal condition or disruption of the childbirth. Conclusions. Failure to progress of labour is the main cause of transfers. The women giving birth for the first time aged 30 and over, admitted for to the BC after 40 weeks of pregnancy and dilation below 4 cm were the most often transferred group of women.